Lifestyles of Spanish elders from supervened SARS-CoV-2 variant onwards: A correlational research on life satisfaction and social-relational praxes - Díaz-García, Orlanda; Herranz Aguayo, Inmaculada; Fernández de Castro, Patricia; Ramos, José Luis Gómez (Frontiers in Psychology, 2022)
Objective. This study aimed to analyse the influence and measurement of the relationship and interaction between the elderly lifestyles after the appearance of the SARS-CoV-2 variant and the factors analysed comprised life satisfaction levels, social relationships, and daily-life activities. Methods. The study population was ≥ 65 in Castile-La Mancha (N = 390,221). The research design was quantitative and arose from primary data collected via an ad hoc survey carried out through the Computer Assisted Telephone Interview system by randomly stratified sampling. The sample size was made up of 1,065 cases, and the participants were selected through a random sampling stratified by gender quotas (55.40% females; 44.60% males), age (), province, and habitat size. Results. Gotten results revealed two main lifestyles, from which a notable behavioural change in personal relationships led to infer towards alternative lifestyles. Conclusion. Notwithstanding the variation in lifestyles of the elderly after the pandemic, certain relationships remained unaltered. Thus, from the analysed variables, relatives and friends relationships were scarcely influenced by the supervened incident.